Statics and Rotational Dynamics of Composite Beams - Ghorashi, Mehrdaad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a comprehensive study of the nonlinear statics and dynamics of composite beams and consists of solutions with and without active elements embedded in the beams. The static solution provides the initial conditions for the dynamic analysis. The dynamic problems considered include the analyses of clamped (hingeless) and articulated (hinged) accelerating rotating beams. Two independent numerical solutions for the steady state and the transient responses are presented. The author illustrates that the transient solution of the nonlinear formulation of accelerating rotating beam converges to the steady state solution obtained by the shooting method. Other key areas considered include calculation of the effect of perturbing the steady state solution, coupled nonlinear flap-lag dynamics of a rotating articulated beam with hinge offset and aerodynamic damping, and static and dynamic responses of nonlinear composite beams with embedded anisotropic piezo-composite actuators. The book is intended as a thorough study of nonlinear elasticity of slender beams and is targeted to researchers, graduate students, and practicing engineers in the fields of structural dynamics, aerospace structures, and mechanical engineering.
Introduction -- Review of the Variational Asymptotic Method and the Intrinsic Equations of a Beam -- Linear Static Analysis of Composite Beams -- Nonlinear Static Analysis of Composite Beams -- Transient Nonlinear Dynamics of Accelerating Hingeless Rotating Blades -- Steady State and Perturbed Steady-State Nonlinear Dynamics of Hingeless Rotating Blades -- Rigid and Elastic Articulated Rotating Composite Blades -- Static and Dynamic Analysis of Beams with Embedded Anisotropic Piezocomposite -- Appendices. .
Keywords: Mechanics, Applied; Solids; Solid Mechanics